CAR:a P2P content addressable andauto-retrievable algorithm for MANET - WU Hua-feng1; SHI Chao-jian1; GAO Chuan-shan2 (Tongxin xuebao, 2011)
To be directed at the unique features of mobile ad-hoc network（MANET） environment,a kind of mobile P2P（MP2P） index structure.Geographic-information-based hierarchical hash index structure（GH2I）,was presented based on DHT（Distributed Hash Table）.On the basis of GH2I,a MP2P resource search and retrieval algorithm CAR（content ad-dressable and auto-retrievable） was further proposed,and a scalable efficient and mobility adaptive MP2P overlay net-work was finally constructed.